2008
DOI: 10.1002/jcb.21904
|View full text |Cite
|
Sign up to set email alerts
|

Negative effects of the amino acids Lys, His, and Thr on S6K1 phosphorylation in mammary epithelial cells

Abstract: The role of essential amino acids (AA) on protein synthesis via the mTOR pathway was studied in murine mammary epithelial cells cultured under lactogenic conditions. Leu, Ile, and Val increased S6K1 phosphorylation compared to that measured in AA-deprived cells. Trp, Phe, and Met had no effect. Surprisingly, Lys, His, and Thr inhibited S6K1 phosphorylation in both murine and bovine mammary cells. Thr exhibited the most potent inhibition, being the only amino acid that competed with Leu's positive role. In non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
49
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 51 publications
12
49
3
Order By: Relevance
“…The latter study demonstrated that synthesis of beta-lactoglobulin in bovine cells was associated with phosphorylation of 4EBP1 and S6K1 and that the major effect on protein synthesis of all AA or Leu was through mTOR. Media containing Leu increased milk protein synthesis, while Lys, His, Thr, or the combination of those AA decreased milk protein synthesis up to 65% via dephosphorylation of S6K1 [163]. Infusion of His and Met+Lys did not depress milk protein synthesis in bovine mammary tissue and Leu infusion only had a numerical increase in protein synthesis, but Leu and Met+Lys increased phosphorylation of S6K1 and RPS6 [164].…”
Section: How Insulin and Mtor Cross-talk Control Translation Of Milk mentioning
confidence: 88%
“…The latter study demonstrated that synthesis of beta-lactoglobulin in bovine cells was associated with phosphorylation of 4EBP1 and S6K1 and that the major effect on protein synthesis of all AA or Leu was through mTOR. Media containing Leu increased milk protein synthesis, while Lys, His, Thr, or the combination of those AA decreased milk protein synthesis up to 65% via dephosphorylation of S6K1 [163]. Infusion of His and Met+Lys did not depress milk protein synthesis in bovine mammary tissue and Leu infusion only had a numerical increase in protein synthesis, but Leu and Met+Lys increased phosphorylation of S6K1 and RPS6 [164].…”
Section: How Insulin and Mtor Cross-talk Control Translation Of Milk mentioning
confidence: 88%
“…Phosphorylation of S6K1 correlates with increased protein synthesis. Prizant and Barash (2008) recently demonstrated that adding Lys, His and Thr decreased phosphorylation of S6K1 in cultures of L-1 cells of bovine mammary gland. Overall, it seems that the availability of AA to the mammary gland and milk protein synthesis is tightly regulated locally and systemically, which may make it difficult to identify potential key regulatory steps susceptible to modification to increase milk protein yield.…”
Section: Factors Affecting the Efficiency Of N Utilization In The Mammentioning
confidence: 98%
“…heat, reduction) (Treweek, 2012). Prizant and Barash (2008) documented that the AAs Lys, His and Thr negatively affect S6K1 phosphorylation in bovine mammary epithelial cells. The decreased α s2 -CN levels in cows fed SSBM may have resulted from the up-regulation of the availability of an essential AA, such as Lys, to stabilize the CN structure.…”
Section: Caseinsmentioning
confidence: 99%